Increased Production Of Corn (Zea Mays, L) Varieties Lamuru, Bisma, Sukmaraga In Marginal Critical Land With The Use Of Cow Manure In North Aceh Regency - Nasruddin; Hafifah; Jamidi Jamidi; Zurrahmi Wirda; Muhammad Albi Ansari Pohan (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2022)
This study aims to determine the technique of increasing the production of corn (Zea mays, l) varieties of lamuru,bisma, sukma raga with marginal critical land with the use of cow manureby North Aceh District. This research was carried out from June to November 2021, at the West Reuleut Gampong Garden, Muara Batu District, North Aceh Regency. This study used a 3 x 2 randomized block design and replicated 3 times. The first factor is varieties with 3 levels, name-ly: Bisma, Lamuru, and Sukmaraga varieties. The second factor is cow manure with 2 levels, namely 15 tons/ha and 20 tons/ha. Parameters observed were plant height, stem diameter, number of leaves, time of flower emergence, cob length, cob weight, length without cob, weightwithout cob, and weight of 1000 seeds. The results showed that the treatment of severalvarieties showed a very significant effect on almost all of the observed variables. The use of bisma varieties showed the best growth. The use of cow manure 15 tons/ha also gives the bestgrowth on almost all variables.